Experimental investigation for quantification and high accuracy of capillary refill time - Mizuno, Takato; Nakamura, Masanori; Sugita, Shukei; Ujihara, Yoshihiro (Transactions of Japanese Society for Medical and Biological Engineering, 2020)
Capillary refill time (CRT), the time required to recover the color of a nail after pressurization on the nail for 5 seconds is released, is a simple indicator for evaluation of circulatory function. Although a previous study attempted to evaluate other circulatory functions from the CRT, such an application has not been put to practical use. By removing factors affecting the unstableness of CRT, the CRT might be used as an indicator to diagnose other medical conditions. As a first step, a quantitative CRT device was fabricated. The device consists of a pressure application part to apply a constant force and a CCD camera to image changes in color on the nail. By fitting an exponential function to the time-course change of the brightness, we obtained a CRT. The CRT was repeatedly measured and we found that the green color image resulted in the most stable CRT.